Genetic and morphometric evidence on a Galápagos Island exposes founder effects and diversification in the first‐known (truly) feral western dog population. Issue 2 (5th December 2013) - Reponen, Sini E. M.; Brown, Sarah K.; Barnett, Bruce D.; Sacks, Benjamin N.
Abstract Domesticated animals that revert to a wild state can become invasive and significantly impact native biodiversity. Although dogs can be problematic locally, only the Australasian dingo is known to occur in isolation from humans. Western dogs have experienced more intense artificial selection, which potentially limits their invasiveness. However, feral dogs eradicated from Isabela Island, Galápagos in the 1980s could be the first‐known exception. We used DNA and morphometric data from 92 of these dogs to test the hypotheses that (i) these dogs persisted independently of humans for up to a century and a half since descending from a handful of dogs introduced in the early 1800s, vs. (ii) similarly to other western feral dog populations, they reflected continuous recruitment of strays from human settlements on a portion of the Island. We detected one dominant maternal lineage and one dominant paternal lineage shared by the three subpopulations, along with low autosomal genetic diversity, consistent with the hypothesized common origins from a small founder population. Genetic diversity patterns among the three island subpopulations were consistent with stepping‐stone founder effects, while morphometric differentiation suggested rapid phenotypic divergence, possibly due to drift and reinforced by selection corresponding to distinct microclimates and habitats on Isabela. Despite the continued presence of free‐ranging dogs in the vicinity of settlements on Isabela and other Galápagos Islands, feral populations have not reestablished in remote areas since the 1980s, emphasizing the rarity of conditions necessary for feralization of modern western dogs.